A cross‐national study of depression in preclinical dementia: A COSMIC collaboration study. Issue 11 (3rd September 2020) - Carles, Sophie; Carrière, Isabelle; Reppermund, Simone; Davin, Annalisa; Guaita, Antonio; Vaccaro, Roberta; Ganguli, Mary; Jacobsen, Erin P.; Beer, Joanne C.; Riedel‐Heller, Steffi G.; Roehr, Susanne; Pabst, Alexander; et al.
Abstract: Introduction: Depression commonly accompanies Alzheimer's disease, but the nature of this association remains uncertain. Methods: Longitudinal data from the COSMIC consortium were harmonized for eight population‐based cohorts from four continents. Incident dementia was diagnosed in 646 participants, with a median follow‐up time of 5.6 years to diagnosis. The association between years to dementia diagnosis and successive depressive states was assessed using a mixed effect logistic regression model. A generic inverse variance method was used to group study results, construct forest plots, and generate heterogeneity statistics. Results: A common trajectory was observed showing an increase in the incidence of depression as the time to dementia diagnosis decreased despite cross‐national variability in depression rates. Discussion: The results support the hypothesis that depression occurring in the preclinical phases of dementia is more likely to be attributable to dementia‐related brain changes than environment or reverse causality.